A heterogeneous Rh/CPOL-BINAPa&PPh3 catalyst for hydroformylation of olefins: chemical and DFT insights into active species and the roles of BINAPa and PPh3. Issue 11 (25th May 2022) - Zhang, Jinrong; Li, Jin; Li, Kechao; Zhao, Jinyu; Yang, Zhengyi; Zong, Lingbo; Chen, Jianbin; Xie, Cong-Xia; Zhao, Xiu-Xiu; Jia, Xiaofei
Abstract : A reusable Rh/CPOL-BINAPa&PPh3 catalyst was used for heterogeneous hydroformylation of olefins, affording the corresponding linear aldehydes with excellent regioselectivities and high TON values. The active Rh–H species were studied in detail. Abstract : Porous organic polymers (CPOL-BINAPa&PPh3 and CPOL-BINAPa&PhPh3 ) were synthesized via copolymerization of a divinyl-functionalized phosphoramidite ligand (2vBINAPa) and various trivinyl-monomers (3vPPh3 and 3vPhPh3 ). After metalation with Rh(acac)CO2, Rh/CPOL-BINAPa&PPh3 showed the better catalytic performance than Rh/CPOL-BINAPa&PhPh3 in the heterogeneous hydroformylation. A corresponding catalytic Rh–H species has been investigated by FT-IR and/or NMR spectroscopy. The results indicated that two kinds of Rh–H species were formed in the Rh/CPOL-BINAPa&PPh3 catalyst. The ee species containing the BINAPa ligand contributed to the high activity in hydroformylation. The three P coordinated Rh–H species consisting of BINAPa and PPh3 ligands resulted in the high regioselectivity owing to the steric hindrance. Furthermore, the DFT calculations and cycle test results of the catalysts indicated that the PPh3 moieties could improve the stability of the Rh–H species, prevent dissociation of Rh from the BINAPa moieties and reduce the loss of Rh in the catalytic process.